When the lights went out what really happened to Britain in the seventies - Beckett, Andy 1969- (Faber and Faber Ltd, 2010)
The seventies encompass strikes that brought down governments, shock general election results, the rise of Margaret Thatcher and the fall of Edward Heath, the IMF crisis, the Winter of Discontent and the three-day week. This title goes in search of what really happened, what it felt like at the time, and where it was all leading.